18F-FDG-PET/CT Imaging in Advanced Glottic Cancer: A Tool for Clinical Decision in Comparison with Conventional Imaging. (11th September 2019) - Paone, G.; Martucci, F.; Espeli, V.; Ceriani, L.; Treglia, G.; Ruberto, T.; Richetti, A.; Piantanida, R.; Giovanella, L.
Abstract : This study assessed the role of 18 F-FDG PET-CT (PET/CT) to detect the cartilage and paraglottic infiltration in advanced glottic cancer comparing the results with those of conventional imaging (CI) (contrast-enhanced computed tomography and/or magnetic resonance). In addition, we assessed the prognostic value of quantitative parameters, measured on baseline PET/CT, in terms of event-free survival (EFS) and overall survival (OS). We retrospectively analyzed 27 patients with glottic squamous cell carcinoma stage III and IVA, treated in our institute between 2010 and 2016, comparing PET/CT, performed for staging and radiotherapy planning, and CI findings. Cohen's K was used to compare concordance between PET/CT and CI. Imaging findings were correlated with endoscopic evaluation and histological reports (gold standard (GS)). All lesions shown by CI were also detected by PET/CT imaging, and in 5 cases, a better definition of local infiltration was achieved with PET/CT than CI (5 CT). Sensitivity, specificity, and accuracy of PET/CT and CT were 95%, 86%, and 93% and 70%, 86%, and 74% for, respectively. MRI showed sensitivity and specificity of 100%. One false-negative (FN) cases and 1 false-positive (FP) case were observed with PET/CT with no difference compared to MRI (10 cases). Six FN cases and 1 FP case were observed with CT. Cohen's K was 0.60 (PET vs. CI) and 0.80 (PET vs. GS). Patients were followed-up for at least 24 months to calculate EFS and OS. 13 local recurrence and 7 deaths were recorded. Among quantitative PET parameters, baseline MTV was the most powerful predictor of outcome. Our data suggest a reliable sensitivity and accuracy of PET/CT in the evaluation of local extension, proving a useful method for initial local staging in addition to the well-established role in lymph-node and distant sites assessment. Furthermore, pretreatment MTV provides better prognostic information than other PET/CT parameters.